Marketing Strategic Drift: Four Causes and Solutions - Alrajhi, Abdulaziz (مجلة العلوم الإدارية و الإقتصادية, 2025)
Purpose: The aim of this study is to explore key causes of marketing strategic drift and empirically testing the effects of these causes on marketing strategic drift. Methodology: A quantitative research design was used to achieve the purpose of this study through collecting data from a sample consisting of marketing managers in service enterprises. The key causes of marketing strategic drift were identified based on a direct review of the literature. Findings: Four key causes of marketing strategic drift were induced from the literature; customer, cognition, innovation, and change orientation. Testing the effects of these four independent variables using structural equation modeling by SmartPLS software pointed out that these variables have significant and negative effects on marketing strategic drift. Value: Service enterprises can avoid marketing strategic drift through finding solutions for customer, cognition, innovation, and change-driven causes of marketing strategic drift, i.e. becoming customer, cognition, innovation, and change-oriented enterprises.